PENERAPAN METODE INFECTION CONTROL RISK ASSESMENT (ICRA) UNTUK MENCEGAH INFEKSI SILANG DI KLINIK JURUSAN KEPERAWATAN GIGI POLTEKKES KEMENKES JAMBI - Junaidi Junaidi; Rina Kurnianti; Pahrur Razi (Jurnal Kesehatan Gigi, 2018)
TITLEAPPLICATION OF THE INFECTION CONTROL RISK ASSESSMENT (ICRA) METHOD TO PREVENT CROSS INFECTION IN NURSING DEPARTMENT OF DENTAL HEALTH CLINICS AT THE MINISTRY OF HEALTH, JAMBIABSTRACTPatients who visit and care for the teeth are particularly susceptible to clinical infections that may occur due to scaling, tooth extraction and non-sterile use of the device. Besides microorganisms around the clinic, infection control practices, and patient's immune system are also risk factors for infection (Kemenkes RI, 2012).Infection Control Risk Assessment (ICRA) is a control system of measurable infection control by looking at the continuity and probability of infectious field-based infection control applications; includes assessment of several important aspects of infection control such as handwashing compliance, prevention of infection spread, contact alert management (Lardo, et al., 2016).The purpose of this research is to know the application of Infection Control Risk Assessment (ICRA) method to prevent cross infection in Clinic of Dental Poltekkes Department of Health Kemenkes Jambi. This research is a quantitative research with quasy expriment method, and data collection from primary data obtained from observation form.The results of the analysis of the application of ICRA method is effective on improving the prevention and control of cross-infection in Dental Clinic of Dental Polytechnic Dental Department of Kemenkes Jambi is shown by significance value at 0.000 (p 0,05). Suggestion of practice student can increase compliance of prevention and control of cross infection with ICRA method in Dental Clinic of Dental Care Poltekkes Kemenkes Jambi.